Materials to the Dictionary of Pishchanyi Brid Village Dialect (Dobrovelychkivka District, Kirovograd Region): Letter F (Linguostylistic Studies, 2018)
Although in recent years, researchers in Ukrainian dialectology have become increasingly interested in the description of dialect lexicon as a dictionary entry, it still lacks systemic consideration. First and foremost, it concerns a theoretical basis for compiling this type of dialect dictionaries, unifying the description and stratigraphy of lexicographic works.The purpose of the article is to present modern speaking lexicon of one village residents and do it as fully as possible. The dialects of the Central Ukrainian region, in particular dialects of the Kirovograd region, are researched insufficiently. An exception is our studies of the geographical vocabulary of Central Ukraine and the monography Semantic Features of Folk Geographical Terminology in the Ukrainian Language. The abovementioned determines the topicality of the issue.The study analyzes a fragment of the dialect lexicon of the village of Pishchanyi Brid of the Dobrovelychkivskyi district residents (Kirovograd region, Central Ukraine) in terms of modern approaches to the lexicographic processing of the vocabulary. Each dictionary entry is illustrated with the maximum number of the recorded examples, examples of quotations from spoken dialect, especially those lexical units which differ from their equivalents in literary language. The dialect dictionary entry opens with a headword in bold placed at the beginning of an entry. After the word, in square brackets, transcription with the obligatory stress indicator and other phonetic features of the lexeme is provided.The article is an attempt to introduce dialect words into the scientific discourse, starting with the letter F. The author of the article, who comes from Pishchanyi Brid, has begun to record the materials in the text file for the initiated dictionary since 1990. This is, in her words, an attempt to “create a dialectical picture of her village”.
Keywords: Ukrainian dialectology; dictionary; lexicography; phraseology; dialectal speech; Pishchanyi Brid village